2011
DOI: 10.3390/ijms12117635
|View full text |Cite
|
Sign up to set email alerts
|

A 1HNMR-Based Metabonomics Study of Postmenopausal Osteoporosis and Intervention Effects of Er-Xian Decoction in Ovariectomized Rats

Abstract: A metabonomics method using 1H nuclear magnetic resonance spectroscopy (1HNMR) was applied to obtain a systematic view of the development and progression of postmenopausal osteoporosis. Using partial least squares discriminant analysis (PLS-DA), 26 and 34 characteristic resonances were found respectively in urine and plasma of ovariectomized rats (Variable importance, VIP value ≥1.0), and the significant altered metabolites identified in the plasma and urine were 10 and 9, respectively. Changes in these metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…Er-Xian decoction, a popular Chinese medicinal formula comprised of Epimedium brevicornum Maxim, Curculigo orchioides Gaertn, Anemarrhena asphodeloides Bge, Phellodendron chinense Schneid, Morinda officinalis How, and Angelica sinensis Diels in a compositional ratio of 9:9:6:6:9:9, has been widely used for treating osteoporosis and relieving menopausal syndrome [59,60,61,62]. Xue et al demonstrated that the administration of Er-Xian extracts could provide satisfactory effects on OVX rats through the metabolomics analysis [51]. Gushudan, which consists of Herba Epimedii , Fructus Cnidii , Rhizoma Drynariae , and Radix Miltiorrhizae at a ratio of 2:1:1:1, has been accepted as a traditional formula for kidney-tonifying and bone-strengthening [63].…”
Section: The Biomarkers and Their Potential Values In Osteoporosismentioning
confidence: 99%
See 2 more Smart Citations
“…Er-Xian decoction, a popular Chinese medicinal formula comprised of Epimedium brevicornum Maxim, Curculigo orchioides Gaertn, Anemarrhena asphodeloides Bge, Phellodendron chinense Schneid, Morinda officinalis How, and Angelica sinensis Diels in a compositional ratio of 9:9:6:6:9:9, has been widely used for treating osteoporosis and relieving menopausal syndrome [59,60,61,62]. Xue et al demonstrated that the administration of Er-Xian extracts could provide satisfactory effects on OVX rats through the metabolomics analysis [51]. Gushudan, which consists of Herba Epimedii , Fructus Cnidii , Rhizoma Drynariae , and Radix Miltiorrhizae at a ratio of 2:1:1:1, has been accepted as a traditional formula for kidney-tonifying and bone-strengthening [63].…”
Section: The Biomarkers and Their Potential Values In Osteoporosismentioning
confidence: 99%
“…Ma et al found that the level of glucose was significantly elevated in rats six weeks after OVX removal surgery [52]. Likewise, Xue et al found the increased level of glucose and lactate in the OVX mice, and the results implied that ovariectomy can affect the energy metabolism and utilization [51]. Estrogen-deficiency induced obesity is associated with fat accumulation and excessive intake of energy that break down the balance of energy metabolism.…”
Section: Biological and Metabolic Significance Of The Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously, global metabolomics using the HPLC-MS/MS method provides corroborative evidence for targeted metabolomics studies. This study attempts to offer metabolomic evidence to explain the fine-tuned systems and complex metabolic networks in bio-systems and to provide a basis for updating and improving the mechanistic study of HPL function in menopausal syndromes (Xue et al, 2011;You et al, 2014;Zhu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is a powerful analytical platform that allows for the assessment of global metabolic profiles in easily accessible biofluids and biomarker discovery in order to distinguish between diseased and non-diseased status information [8] as well as for the evaluation of drug toxicity and gene function [9]. A number of new analytical technologies have been employed for metabolomics analysis, including 1 H-NMR [10], ultra-high-performance liquid chromatography quadrupole-time-of-flight/high-sensitivity mass spectrometry (UPLC-Q-TOF/HSMS) [11], UPLC-electrospray ionization/MS (UPLC-ESI/MS) [12], gas chromatography/MS [13] and others.…”
Section: Introductionmentioning
confidence: 99%